serum Levels of sodium and Potassium in Patientswith Asthma on Salbutamol Therapy - S. Ahmed, Salam; O. Al-janabi, Hassna; A. Zbaar, Sami (Tikrit Journal of Pharmaceutical Sciences, 2023)
A total of 150 patients with asthma on salbutamol therapy were included in this study along with 90 apparently healthy adult person ( control group) were investigated for the measurements of serum sodium and potassium levels. All patients and controls were fasting when sampleds Sodium and potassium serum levels have been performed by using flame photometer. All patients showed a normal serum sodium (mean 139.8 mmol/L)while the majority (73.4%) of the patients showed hypokalemia (mean 3.1 mmol/L)when compared to control. This study showed that salbutamol have no deteriorated effect on sodium, while it may reduce potassium levels in the majority of patients.